Economic Growth, International Technological Spillovers and Public Policy: Theory and Empirical Evidence from Asia - Robert E. Evenson; Lakhwinder Singh (Yale University, Economic Growth Center, 1997)
This paper examines, within the new growth theory framework, the contribution of international technological spillovers using panel data for eleven Asian countries over the period 1970-93. A country's productivity growth is shown to depend not only on its domestic R&D investment but also on the R&D investment of its trading partners. The evidence for such positive international technological spillovers is strong. This paper also shows that the beneficial effects of international technological spillovers on productivity growth are stronger in South East Asian countries than that of of South Asian countries.
Keywords: 330; Economic Growth; Technology Spillovers; Asia; Neue Wachstumstheorie; Technischer Fortschritt; Spillover-Effekt; Internationale Wirtschaftsbeziehungen; Theorie